1995
DOI: 10.1093/clinids/21.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Stool Carriage, Clinical Isolation, and Mortality During an Outbreak of Vancomycin-Resistant Enterococci in Hospitalized Medical and/or Surgical Patients

Abstract: During a nosocomial outbreak of infection due to vancomycin-resistant enterococci (VRE), rectal swabs that were collected weekly were used to identify and isolate VRE carriers. Over 6 months, 1,458 stool specimens from 724 high-risk patients were cultured, and 187 VRE isolates were recovered from 61 patients; 96% of the isolates were Enterococcus faecium. VRE tended to be isolated from clinical specimens from patients identified as VRE carriers by stool surveillance (P < .01). However, isolation of VRE from su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
1
4

Year Published

1997
1997
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(96 citation statements)
references
References 17 publications
0
91
1
4
Order By: Relevance
“…Educational classes on the importance of VRE were given in group sessions, and guidelines were posted in each unit. We emphasize the growing importance of the vancomycin-resistant enterococci as nosocomial pathogens, causing, besides colonization, severe infections, such as bacteremias, urinary-tract and surgical-site infections [3,28]. The therapeutic arsenal presently available is quite scarce, with accounts of resistance to recently developed drugs (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Educational classes on the importance of VRE were given in group sessions, and guidelines were posted in each unit. We emphasize the growing importance of the vancomycin-resistant enterococci as nosocomial pathogens, causing, besides colonization, severe infections, such as bacteremias, urinary-tract and surgical-site infections [3,28]. The therapeutic arsenal presently available is quite scarce, with accounts of resistance to recently developed drugs (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, enteric VRE colonization usually precedes infection (115). The lower intestinal tract is the most frequently colonized site, and persistent enteric colonization, especially among those with frequent hospital readmissions, may be a prominent VRE reservoir.…”
Section: Emergence Of Antimicrobial Resistancementioning
confidence: 99%
“…As in the first 5 years of the epidemic, 14 most investigators have not succeeded in recovering VRE from the hands of HCWs 16 or have recovered VRE on culture of hands from a very small percentage of HCWs. 26 Unlike the findings of the latter studies, Bonilla and colleagues recovered VRE from the hands of 13% to 41% of HCWs over 3 years in a long-term-care unit. 27 In a mathematical model of transmission dynamics, persistence, and the impact of infection control programs on VRE in an intensive care unit setting, Austin and colleagues showed that the prevalence of contamination of HCWs' hands was very low, even though the incidence may have been high, and offered this observation as an explanation for the low recovery of VRE from cultures of HCWs' hands.…”
Section: Glen Mayhall MDmentioning
confidence: 79%